1980
DOI: 10.1084/jem.152.5.1424
|View full text |Cite
|
Sign up to set email alerts
|

Production of predominantly polymeric IgA by human peripheral blood lymphocytes stimulated in vitro with mitogens.

Abstract: Human peripheral blood lymphocytes (PBL) were cultured for various time periods (up to 8 d) in the presence of pokeweed mitogen (PWM), lipopolysaccharide, or Epstein-Barr virus. Cell-free supernates were fractionated on a standardized ultrogel AcA 22 column and the proportion of polymeric and monomeric IgA was determined by radioimmunoassay. The results demonstrate that PBL stimulated with these mitogens produce IgM and IgG with molecular characteristics identical to those found in serum, but that the IgA prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(33 citation statements)
references
References 15 publications
1
32
0
Order By: Relevance
“…Previous experiments demonstrated a predominance of IgA~ plasma cells early in the P W M response, at days 3 and 4; however, by day 7 of culture, the proportion of IgA2 plasma cells was equal to that of IgA1 (5). This suggested that the maturation of IgA2 plasma cells might be delayed compared with that of IgA1, and that if the culture period were extended, higher concentrations of IgAz might be found in culture supernatants.…”
Section: Resultsmentioning
confidence: 65%
“…Previous experiments demonstrated a predominance of IgA~ plasma cells early in the P W M response, at days 3 and 4; however, by day 7 of culture, the proportion of IgA2 plasma cells was equal to that of IgA1 (5). This suggested that the maturation of IgA2 plasma cells might be delayed compared with that of IgA1, and that if the culture period were extended, higher concentrations of IgAz might be found in culture supernatants.…”
Section: Resultsmentioning
confidence: 65%
“…In contrast, IgA and IgM antibodies to both RR extract and Ag I/II increased by days [21][22][23][24] in both parotid saliva and tears from all subjects studied but one (donor 3). Individual values are presented as in Table 1.…”
Section: Methodsmentioning
confidence: 96%
“…2 Indicative of their generation in mucosal immune responses and very similar to plasmablasts circulating during steady state, 1 more than one-half of plasmablasts/ plasma cells detectable before and throughout B-cell depletion therapy expressed IgA, and the same cells predominantly coexpressed CCR10 and to a lesser extent ␣ 4 ␤ 7 integrin. 23,24 The IgA secreted by these plasmablasts in patients with RA showed rheumatoid factor reactivity only in single patients, whereas secretion of antimicrobial antibodies was detected in all patients as well as controls. In this regard, commensal microbes specifically induce secretory IgA production in the intestine of normal mice.…”
Section: Discussionmentioning
confidence: 99%